Dual-Loop Virtual Synchronous Machine to Enhance Frequency and Voltage Stability in PV-Hydro Microgrids - Adhikari , Titikshyu; Khatiwada, Vesuvius; Khadka, Supreme; KC, Sanju; Kumar Chaudhary, Paras; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2026)
This paper investigates a dual-loop Virtual Synchronous Machine (VSM) to enhance frequency and voltage stability in a PV-Hydro microgrid supplemented by a lithium-ion storage battery system. The proposed VSM simultaneously emulates the inertia and damping property of a synchronous generator and mitigates the voltage dip problem during transient period due to the large perturbation of P-Q load.  The VSM injects active and reactive power during transient period through an inverter with a storage battery at dc side. MATLAB/Simulink simulations were carried out under severe load disturbances for two cases: (i) PV-Hydro micro-grid without VSM, (ii) PV-Hydro micro-grid with proposed dual-loop VSM. Without VSM support, frequency and voltage dropped to 0.57 pu and 0.78 pu respectively during transient period, exhibiting unstable behaviour. The proposed dual-loop VSM improved stability, limiting frequency deviation to 0.86 pu and voltage sag to 0.9 pu with faster recovery during transient period.